Optimization of process variables for enhanced lactic acid production utilizing paneer whey as substrate in SMF - Abhishek Dutt Tripathi (Applied Food Biotechnology, 2015)
The production of lactic acid from dairy by-product (paneer whey) via SMF by Lactobacillus delbruckii was optimized in the present study.  Three process variables viz; inoculum size, temperature and pH were optimized using CCRD. Design Expert 8.0.2.0 trial depicted that an optimum concentration of 8.00 % (v/v) size of inoculum, 5.50 pH and 36.53 °C temperature gave lactic acid and biomass yield of 5.61 g/L and 4.27 g/L, respectively. Lactic acid production was scale up in 7.5 L bioreactor under optimized conditions and it gave lactic acid and biomass yield of 39.2± 1.4 and 47.6 ±0.8 g/L, respectively.  µg, YP/S, YP/X and productivity were found to be 0.14 h-1, 0.66 g/g, 0.70 g/g and 1.98 g/L. h, respectively. Leudking Piret equation deduced that lactic acid production was growth associated which varies from earlier reports. Lactic acid was characterized by FTIR and HPLC.